COVID-19 risk perception among students at a state university in Chile - Matar-Khalil, Shadye (2024)
Objective: To evaluate the level of COVID-19 risk perception (PCR-CV19) by returning to in-person classes and to analyze this perception with sociodemographic and health variables associated with such disease. Materials and methods: A cross-sectional and prospective study. The questionnaire was adapted to assess the PCR-CV19 among 532 university students. Moreover, an association analysis of the four dimensions of the PCR-CV19 (cognitive vulnerability, emotional vulnerability, risky-protective behaviors and severity) and the perception index was performed with sociodemographic and health variables. The following statistical methods were used: one-way analysis of variance (ANOVA), Shapiro-Wilk test for normality, Levene’s test for homogeneity of variances and Tukey’s honest significant difference or Games-Howell post hoc tests. These analyses were performed using the Jamovi statistical software, version 1.2.2. Results: A moderate level of PCR-CV19 was found, where the most relevant dimensions were risky-protective behaviors and severity. In addition, there was an association between the dimensions PCR-CV19 and perception index with the variables age, gender, alcohol consumption, physical and mental health indicators (anxiety and depression), and experiences with COVID-19. Cognitive vulnerability and emotional vulnerability were the most sensitive dimensions in the evaluation of the PCR-CV19. Conclusions: We continue to face constant risk conditions, thus making it necessary to maintain a surveillance scheme of the PCR-CV19 experienced by the population. In university students, cognitive vulnerability and emotional vulnerability were the most sensitive dimensions in the evaluation of PCR-CV19 and experiences with COVID-19 (illness or death). The fact that university students do not feel vulnerable and/or do not perceive the severity associated with COVID-19 transmission may affect their self-care behaviors. These results have key implications for public health; therefore, an intersectoral approach is required to have relevant information in order to face future pandemics.